Ethnic-racial thinking: scientific knowledge, legal norms and education (Práxis Educativa, 2022)
This research focuses on the analysis of narratives about the formulation of ethnic-racial thinking from Raimundo Nina Rodrigues’s academic productions carried out in the late nineteenth century. The purpose is to highlight how the narratives were constructed to include or not the indigenous and the black people in discursive textualities considering their power of naming, classification and hierarchization. In this study, legal devices were incorporated, corresponding to the Constitutions of the 19th and 20th centuries, in order to demonstrate tensions and detachments in the Brazilian ethnic-racial thinking. The analyzes were made using as theoretical support the philosophy of difference, with an emphasis on Foucault and the Cameroonian professor Achille Mbembe’s considerations. In the results, it is highlighted the symbolic power of institutional language used in scientific texts and legal provisions to segregate and degrade the indigenous and black people, being called as peoples who are: wild, barbarians, indolent, lazy and dangerous, to the detriment of civilized white people.Keywords: Ethnic-racial thinking. Degeneration theory. Philosophy of difference. Education.